Identification and comparative analysis of potholes using image processing algorithms - Anik, Fahim Shahriare; Ahmed, Asif; Maheen, Avita; Alam, Puily (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.